2018
DOI: 10.1186/s40695-018-0042-1
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptive challenges and the transgender individual

Abstract: In recent years public awareness of healthcare disparities experienced by transgender individuals throughout the world have garnered increasing attention within the media and from health advocates. Despite this increasing awareness, a paucity of research data and clinical protocols of care for clinicians continues to exist, especially in regard to the transgender individual's family planning needs. Clinicians should be on the forefront of promoting strategies that forge a meaningful and collaborative relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…A few participants reported the use of OCPs for the enhancement of female features. Studies showed that the use of OCPs, in this case, may indicate a transgender tendency in males [ 40 , 41 ]. This low incidence is expected since homosexuality is still socially unacceptable and the lesbian, gay, bisexual, and transgender (LGBT) community in Jordan face a great deal of discrimination, and stigmatization, in spite of the fact that the country’s laws ended the criminalization of homosexuality since 1951 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few participants reported the use of OCPs for the enhancement of female features. Studies showed that the use of OCPs, in this case, may indicate a transgender tendency in males [ 40 , 41 ]. This low incidence is expected since homosexuality is still socially unacceptable and the lesbian, gay, bisexual, and transgender (LGBT) community in Jordan face a great deal of discrimination, and stigmatization, in spite of the fact that the country’s laws ended the criminalization of homosexuality since 1951 [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 Furthermore, hormonal contraceptives such as combined oral contraceptive pills are not indicated for transgender men on masculinizing therapy. 7 Other contraceptive options are less likely to interfere with masculinizing hormone therapy in transgender men, including intrauterine devices, injectables (Depo Provera), and transdermal implants (Nexplanon), however, these may not necessarily aid in the management of acne vulgaris. Currently, iPLEDGE does not provide written guidance to providers on how to register transgender individuals.…”
Section: Discussionmentioning
confidence: 99%
“…A.Francis, S. Jasani et al [22]address the awareness of healthcare disparities experienced by transgender men in midlife, including their contraceptive needs and pregnancy desires. Clinicians should be on the forefront of promoting strategies that make collaborative relationship with the transgender man, including as he transitions through to the menopause and his sexual and reproductive healthcare needs paper in the given email address of the journal.…”
Section: Issue and Challenges Of Adopting Contraception Methods By Mementioning
confidence: 99%